Application of Regularized Meshless Method with Error Estimation Technique for Water–Wave Scattering by Multiple Cylinders - Kue-Hong Chen; Jeng-Hong Kao; Yi-Hui Hsu (Journal of Marine Science and Engineering, 2024)
In this manuscript, we will apply the regularized meshless method, coupled with an error estimation technique, to tackle the challenge of modeling oblique incident waves interacting with multiple cylinders. Given the impracticality of obtaining an exact solution in many real engineering problems, we introduce an error estimation technique designed to achieve reliable solutions. This technique excels in providing dependable solutions that closely approximate analytical solutions. An additional advantage is its capacity to identify the optimal number of points for both source and collocating points, thereby enhancing computational efficiency. The validity of the proposed method will be demonstrated through three numerical cases, presenting results that exhibit substantial agreement.